Significant flow velocity reduction at the intracranial aneurysm neck after endovascular treatment leads to favourable angiographic outcome: a prospective study. Issue 3 (1st February 2021) - Tian, Zhongbin; Liu, Jian; Kumar, Jay; Li, Wenqiang; Zhang, Yisen; Zhang, Ying; Wang, Kun; Wang, Shengzhang; Ren, Zeguang; Yang, Xinjian
Abstract : Background: With widely usage of flow diverter in intracranial aneurysm treatment, some previously used predictors may not be effective in evaluating the recurrence risk. We aimed to comprehensively re-evaluate the predictors of intracranial aneurysm outcome with various endovascular treatment methods and devices. Methods: This is a prospective registered study. We analysed 6-month and 18-month follow-up angiographic data from the prospective study. Data on patient demographics, aneurysm morphology and type of treatment were recorded. Patient-specific haemodynamic simulations were performed. An unfavourable angiographic outcome was defined as recurrence of aneurysm in cases with coiling or stent-assisted coiling, patency of aneurysm in cases with flow diverters or retreatment during follow-up. Results: In total, 165 patients (177 intracranial aneurysms) with at least one angiographic follow-up data were analysed. For the short-term (6-month) results, after univariate analysis, the demographic, morphological and treatment-related factors did not achieve significantly statistical differences. The reduction ratio (RR) of velocity at aneurysm neck after embolisation was significantly lower in the unfavourable angiographic group than the favourable angiographic outcome group (p=0.002). After the Cox regression analysis, the RR of velocity at aneurysm neck was the only independent factor associated with favourable angiographic outcome (OR 0.028; p=0.001) and had an acceptable area under the curve (0.714) with a clear cut-off value (46.14%). Similarly, for the analysis of midterm (18-month) results, the RR of velocity at the aneurysm neck was the only independent significant factor for the unfavourable angiographic outcome (OR 0.050; p=0.017). The area under the curve was 0.754 and the cut-off value was 48.20%. Conclusions: The haemodynamics showed an independent effect on angiographic follow-up results and may provide helpful suggestions for clinical practice in the future.